2019
DOI: 10.2478/midj-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Revitalizing Rural Tourism through Creative Tourism: the Role and Importance of the Local Community

Abstract: Creative tourism is a current topic, yet most of the research is focused on the urban context, with few articles focusing on how creativity can be used and developed in the setting of rural tourism. Furthermore, the theoretical elements identified in this article can become checkpoints through which better strategies for sustainable rural tourism can be developed in the future. Although rich in culture, Romanian villages have not developed their rural tourism offer to its full potential, partly because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Remoaldo conducted factor analysis method and cluster analysis method, studying creative tourism participants from 40 pilot institutions, which were selected for the CREATOUR project based on their sociodemographic characteristics and tourism behaviors, and he obtained three clusters of novelty seekers, knowledge and skills learners, and casual creativity seekers [39]. Souca, Marques and Li discussed the design of creative tourism in villages, cities and communities, analyzed the importance of communities and local individuals in creative tourism and rural revitalization, proposed a "playable city" concept, and continued the discussion on the "creative landscape" [40][41][42]. Ross relied on the perspective of participatory cocreation to analyze how creative tourism promotes the cocreation of stories about archaeological heritage and solves heritage protection issues.…”
Section: Cultural Creativity and Creative Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Remoaldo conducted factor analysis method and cluster analysis method, studying creative tourism participants from 40 pilot institutions, which were selected for the CREATOUR project based on their sociodemographic characteristics and tourism behaviors, and he obtained three clusters of novelty seekers, knowledge and skills learners, and casual creativity seekers [39]. Souca, Marques and Li discussed the design of creative tourism in villages, cities and communities, analyzed the importance of communities and local individuals in creative tourism and rural revitalization, proposed a "playable city" concept, and continued the discussion on the "creative landscape" [40][41][42]. Ross relied on the perspective of participatory cocreation to analyze how creative tourism promotes the cocreation of stories about archaeological heritage and solves heritage protection issues.…”
Section: Cultural Creativity and Creative Tourismmentioning
confidence: 99%
“…Thus, places undergo a series of chain reactions that make them gradually lose their uniqueness [45]. However, in some places that benefit from an advantageous location but lack creative production strategies (such as traditional villages or villages with heritage value), highlighting cultural value and creative production are particularly important [40].…”
Section: Cultural Creativity and Creative Tourismmentioning
confidence: 99%
“…The study showed that not only the urban areas, but also the Romanian rural areas have residents endowed with abilities necessary in developing creative tourism. The main conclusion was that to revitalize the Romanian rural tourism, the entire local community needs to be involved in the tourism planning process, not just the ones with direct ties to it [18].…”
Section: Introductionmentioning
confidence: 99%